(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2016)
We consider strong at-subsets of the Euclidean space R^n and estimate from below the growth of the maximal cardinality of such subsets (our method essentially differs from that of [6]). We then apply some properties of strong at-sets to the illumination problem.